STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK BUDI PEKERTI SISWA - Ratna Dewi; Ahmad Nurkholeq; Andi Sugiartu (STIT PRINGSEWU, 2023)
The teacher's strategy for Islamic Religious Education (PAI) is very important in the Development of Student Characteristics, because it is not enough to just learn Good Characteristics, without a strategy to form a good personality. Seeing the phenomenon that occurred at SD Negeri 1 Padang Cahya, Balik Bukit District, West Lampung Regency T/A. 2022, students fight with each other, and go in and out of class without permission. The aims of this study were first, to find out the ethics of students, second, to find out the strategies of Islamic religious education teachers in fostering morals and third, to find out the supporting and inhibiting factors of Islamic religious education teachers in fostering morals for fifth grade students at SD Negeri 1 Padang. Light, N/A. 2022. This research is a qualitative research. The population of this study were all students of SD Negeri 1 Padang Cahya West Lampung T/A. 2022, while the sample from this study was students of Class V (five) at SD Negeri 1 Padang Cahya. Data was collected using data collection techniques in the form of observations, questionnaires, interviews and documentation. After analyzing the data, in general the manners of class V students at SD Negeri 1 Padang Cahya, T/A. 2022 can be said to be moderate because 30 respondents 18 people or 72% fall into the medium category. Whereas in the good category only 5 people or 12% and those in the less category are 7 people or 16%. Based on the results of observations and interviews with Islamic Religious Education teachers at Padang Cahya 1 Public Elementary School, they explained that the strategy that can be used to foster student morals is to use various methods, namely: Exemplary, Advice, Discussion, Punishment.